(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chronic wounds are extremely prone to infection motivating the use of advanced dressing that is proactive in healing. This paper has built a hydrogel containing zinc oxide nanoparticle (ZnO-NP) to improve the capabilities of antibacterial wound dressing. ZnO-NPs have been prepared through the precipitation method and embedded into a polyvinyl alcohol and chitosan matrix. The composite was strictly defined in order to determine its characteristics. Fourier-Transform Infrared (FTIR) spectroscopy and X-ray Diffraction (XRD) confirmed that ZnO was formed and specific in the hydrogel. The morphology of the nanoparticle was Scanning Electron Microscopy (SEM) that displayed a porous morphology that is advantageous in terms of antibacterial action. The gel had a high swelling ratio (approximately 200-300%), which is important in absorption of exudates, but with slightly less than the pure hydrogel as it had a denser network. Mechanically, the composite possessed a greater tensile strength (1.5 MPa) and amazing elasticity (200 percentage elongation in break). Through thermal analysis, the stability of ZnO was determined up to 600degC making it stable during the processing. Importantly, the ZnO-entrained hydrogel exhibited high dose-dependent antibacterial activity of Staphylococcus aureus and Escherichia coli. The findings indicate that the fabricated composite is capable of incorporating the necessary wound dressing characteristics: the ability to manage moisture excellently, promote mechanical strength, and provide anti-bacterial activity, thus the composite is a highly promising wound care candidate.